Implementasi Model Kampanye Komunitas Traditional Games Returns dalam Mencegah Adiksi Gawai pada Anak - Aghnina Wahdini; Lestari Nurhajati (Communications, 2019)
Traditional games are Indonesian cultural heritage that need to be preserved by all Indonesian people, especially children. These games have many positive values such as honesty, cooperation and solidarity. In this digital era, Indonesian children no longer know traditional games because of the rapid advances in technology and environmental factors. Since early childhood they have been introduced to online devices and games. Therefore, Traditional Games Returns community create a campaign to invite and teach Indonesian children to play traditional games as an effort to prevent gadget addiction since early stage. This research aims to explore the implementation of Traditional Games Returns community campaign model to prevent gadget addiction in children using the Oostegard campaign model. This research uses qualitative approach and data collection techniques by conducting interviews. The sources in this study were campaign practitioners, child clinical psychologists and the core team of Traditional Games Returns community. The results of this study indicate that this community campaign model is in accordance with the Oostegard campaign model by fulfilling elements of the problem, campaign, knowledge, skills, attitudes, behaviour and reduced problems. Keywords: campaign, traditional games, gadget addiction